Unveiling Salafi Puritanism Indoctrination: A Case Study of an Islamic Boarding School for Girls in Malang - Muhammad Dalle (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Abstract The objective of this research is to investigate the influence of Salafi puritanism thought within the boarding school environment in Malang by depicting an undisclosed educational institution, focusing on its various aspects such as teacher support, curriculum materials, religious practices, and the dominance of Salafi lectures. The study employed qualitative research methods, including interviews, observations, and document analysis, to gather data from teachers, students, and school materials. The findings indicate a significant influence of Salafi puritanism thought in school. Teachers expressed support for Salafi teachings, as evidenced by their instructional methods, choice of source materials, and rejection of certain religious programs. The use of Salafi scholars' books in the religious curriculum and the exclusion of practices such as reciting the Shalawat Nariyah and celebrating additional Islamic holidays provide tangible evidence of this influence. Furthermore, variations in dhikr practices were observed, following the formula of Salafi scholars and differing from mainstream Islamic practices. Salafi preachers dominated the lecture sessions, while alternative perspectives were often disregarded or opposed by Salafi teachers. These indicators reflect the prevailing Salafi puritanism ideology within the school's educational environment. In light of these findings, it is recommended that the school administration considers promoting intellectual diversity. Creating an inclusive environment that acknowledges and respects diverse thoughts and religious perspectives is crucial.